Электронные образовательные ресурсы в обучении цветоведению - Sveshnikova T. K. (Current trends in the development of education system, 2019)
The article considers the issues of design and content of modern learning electronic educational resources, lists the advantages and negative factors regarding the use of these resources in the learning process. Achievements of the advantages and minimization of the negative effects of electronic resources in the modern educational space examines the discipline "Pedagogical design", offering the tools necessary to develop effective, attractive and understandable for students of digital educational materials. Color science "for future artists-teachers.
Keywords: визуализация информации; интерактивность; interactivity; электронный образовательный ресурс; педагогический дизайн; Keywords: electronic educational resource; pedagogical design; visualization of information